Adaptive resource allocation scheme for cognitive radio vehicular ad‐hoc network in the presence of primary user emulation attack. Issue 1 (1st January 2017) - Das, Deepa; Das, Susmita
Abstract : Following the characteristics of the cognitive radio (CR) and the exponential increase of the vehicles, it is envisioned to deploy CR in vehicular ad‐hoc network (VANET) in near future. Due to the mobility of the vehicles, it is quite challenging to find the vacant band and to reuse it for data transmission purpose without affecting the primary network. Further, the presence of primary user emulation attack (PUEA) in the VANET makes this task more complicated. Hence, an accurate detection technique and proper power allocation to the vehicular secondary users (VSUs) are the two major factors which need to be addressed for reliable data transmission. Hence this study attempts to evaluate the performance metrics of the CR‐VANET considering the spatial correlation among the local decisions of the VSUs in the presence of PUEA. The energy efficiency maximisation with adaptive power allocation to the VSUs is achieved by the authors' proposed scheme based on genetic algorithm under the constraints of interference power to the primary receiver, minimum achievable data rate and maximum transmission power limit. The system performance is investigated in detail through the simulation‐based study and analysis.